2020
DOI: 10.1002/jmv.26711
|View full text |Cite
|
Sign up to set email alerts
|

HBV S antigen evolution in the backdrop of HDV infection affects epitope processing and presentation

Abstract: Introduction HBV can evolve under selection pressure exerted by drugs and/or host immunity, resulting in accumulation of escape mutations that can affect the drug or the immune activity. Hepatitis delta virus (HDV) coinfection is also known to exert selection pressure on HBV, which leads to selective amplification of certain mutations, especially in genes that are required for HDV pathogenesis, such as HBsAg. However, little is known about the function of these mutations on HBV or HDV life cycle. The purpose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Interestingly, a study by Sajjad et al revealed unique mutations in the HBsAg gene, which were only observed in HDV/HBV-coinfected patients. For instance, the tryptophan at position 196 of HBsAg was mutated to leucine in almost all HDV/HBV-coinfected patients, although none of the HBV-monoinfected patients carried this mutation [ 241 ]. The tryptophan at position 196 was previously shown to be essential for HBsAg and L-HDAg interaction.…”
Section: Increased Quasispecies Formation Of Hbv By Coinfection With Hdvmentioning
confidence: 99%
“…Interestingly, a study by Sajjad et al revealed unique mutations in the HBsAg gene, which were only observed in HDV/HBV-coinfected patients. For instance, the tryptophan at position 196 of HBsAg was mutated to leucine in almost all HDV/HBV-coinfected patients, although none of the HBV-monoinfected patients carried this mutation [ 241 ]. The tryptophan at position 196 was previously shown to be essential for HBsAg and L-HDAg interaction.…”
Section: Increased Quasispecies Formation Of Hbv By Coinfection With Hdvmentioning
confidence: 99%
“…Some of these mutations affected the generation of proteasomal sites, binding of HBsAg epitopes to MHC-I and -II ligands, and subsequent generation of T- cell epitopes. Selective amplification of these mutations at certain strategic locations might not only enable HBV to counteract the inhibitory effects of HDV on HBV replication, but also facilitate its survival by escaping the immune response ( 132 ). The percentage of conserved HBsAg-positions was significantly higher in HBV/HDV coinfection than HBV monoinfection.…”
Section: Immune Mechanisms and Hbsag Serum Level Changes In Hbv Coinf...mentioning
confidence: 99%